2009
DOI: 10.1002/cii.407
|View full text |Cite
|
Sign up to set email alerts
|

Development of the computerized Mandarin Pediatric Lexical Tone and Disyllabic-word Picture Identification Test in Noise (MAPPID-N)

Abstract: MAPPID‐N was developed to assess the speech‐recognition abilities in noise of Mandarin‐speaking children on disyllabic words, and lexical tones in monosyllabic words, in a picture‐identification test format. Twenty‐six normal‐hearing children aged four to nine years listened repeatedly to the test materials where noise was spatially mixed with or separated from speech, in different signal‐to‐noise (SNR) ratios, to obtain performance‐SNR functions and SNR for 50% correct scores (SNR‐50%). SNR‐50% improved with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…To date, there are three existing tone perception test materials: (1) the Mandarin early speech perception test (MESP) [18], (2) the Mandarin pediatric lexical tone and disyllabic-word picture identification test in noise (MAPPID-N) [20], and (3) the set of standard and method for evaluation of hearing-impaired children's hearing and speech ability [21]. However, these test materials have some limitations.…”
Section: Mandarin Tone Perception Testmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, there are three existing tone perception test materials: (1) the Mandarin early speech perception test (MESP) [18], (2) the Mandarin pediatric lexical tone and disyllabic-word picture identification test in noise (MAPPID-N) [20], and (3) the set of standard and method for evaluation of hearing-impaired children's hearing and speech ability [21]. However, these test materials have some limitations.…”
Section: Mandarin Tone Perception Testmentioning
confidence: 99%
“…First, vocabulary within the daily repertoire of children aged 7 or above was selected. Second, words that are familiar to young children [20,24] were used, because previous study showed that the error rate in tone perception test is closely related to the familiarity of the words [25]. Third, monosyllables were used because they are very common in Chinese.…”
Section: Materials and Equipmentmentioning
confidence: 99%
See 3 more Smart Citations